Profile analysis of population based on age-group in Sumatra - Usman, Mustofa; Barusman, Yusuf S.; Elfaki, Faiz Ahmed Mohamed; Daoud, Jamal Ibrahim (IDOSI Publications, 2013)
The aims of this study is going to analyze the profile of the population in Sumatra based on the age-groups of the population. The Sumatra Island was divided into ten provinces. The profile analysis is going to use to compare the profile of the proportion of age-groups population among the ten provinces. The test of parallel for the profiles, some provinces are significantly different. The variations of the age-goup1 to age-group8 are more variation than the age-group9 to age-group16. The multiple comparison by Tukey’s LSD methods also shows that there are significant difference of proportion of age-groups for some provinces.